Eugeniusz S. Kruszewski, Polskie tropy nad Sundem i Skagerrakiem, Instytut Polsko-Skandynawski, Kopenhaga 2009, ss. 395 / Michalina Petelska. - Petelska, Michalina
Recenzja książki: Polskie tropy nad Sundem i Skagerrakiem / Eugeniusz S. Kruszewski. - Kopenhaga, 2009.